ANALYSIS OF THE RELATIONSHIP BETWEEN FAMILY AND ENVIRONMENTAL FACTORS WITH FAMILIES AT RISK OF MOTHERHOOD STUNTED CHILDREN IN AGAM REGENCY AREA: FAMILY AND ENVIRONMENTAL FACTORS - Sari, Westri Wulan; Symond, Denas; Syahrial, Syahrial (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Stunting prevalence in Agam Regency continues to rise, making it the highest in West Sumatra. This condition is influenced by various family factors—such as number of children, birth spacing, and age at marriage—as well as environmental factors like access to clean water and adequate sanitation. Therefore, this study aims to analyze the relationship between family and environmental factors and the risk of mothers giving birth to stunted children, as a basis for more targeted preventive interventions. Methods: This quantitative study used a cross-sectional design and was conducted in Agam Regency from September 2024 to May 2025. A total of 398 families were selected from 67,429 families based on BKKBN data. Data were collected through questionnaires and analyzed using the Chi-Square test to assess variable relationships, and logistic regression to identify dominant factors influencing the risk of stunting in mothers. Results: The study in Agam Regency found a significant relationship between various family and environmental factors and the risk of mothers giving birth to stunted children. Chi-Square tests showed that the number of children, birth spacing, extreme marriage age, source of drinking water, and sanitation were all significant (p < 0.05). Logistic regression identified the drinking water source as the most dominant factor (p = 0.019). These findings highlight the importance of access to clean water and proper sanitation in preventing stunting at the family level. Conclusion: This study concludes that family and environmental factors significantly influence the risk of mothers giving birth to stunted children, with the source of drinking water identified as the most dominant factor. Therefore, improving access to clean water and providing nutrition education-particularly for pregnant women and mothers of children under five-is crucial in preventing stunting.